Sistem Pengelolaan Arsip Pada Kelurahan Sukaluyu Kecamatan Cibeunying Kaler Berbasis Website - Yusup Miftahuddin; Marisa Premitasari; Galih Al Hakim; Adam M Afriazi; M Razi Saefunazar; Naufal Nurul Hadi H; Abdurrafi Fawwaz (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
Kelurahan is administratively located at the lowest level in the government system in Indonesia. The kelurahan has the task of serving the community. Archives have a role as a memory and source of information, one of which in the Sukaluyu sub-district, Cibeunying Kaler sub-district, Bandung city. Based on observations at the Sukaluyu sub-district office, that the condition of archive management in the kelurahan still has deficiencies, namely the filing system is still in physical form, some documents have been damaged and some missing due to the archival system implemented by this kelurahan still manually. With that, a digital archive management system was created is making website for archive management. This community service is one that is carried out by the lecturer staff and students of the ITENAS informatics study program. This system expected to help increase the effectiveness of archival data management, reduce archive loss, and shorten archive search time.